INCIDENTAL FOREIGN VOCABULARY ACQUISITION THROUGH BINGE-WATCHING KOREAN DRAMAS - Quiñones, Rolando P; Ocampo, Anne Catherine Narciso; Moreño, Dyan Racel Suan; Onod, Steward Cabrera; Otañez, Florie Orbigoso; Palayon, Alyssa Limpiado (Universitas Pamulang, 2022)
From reading activities to media consumption, studies about incidental vocabulary acquisition have progressed through the â€œgermination and molding stages and have emerged to a comprehensive development stageâ€ (Tang, 2020). Given that one of the established productive instructional tools that can help in expanding a learnerâ€™s language skill is watching subtitled foreign films (Kabooha, 2016), the researchers investigated the relationship between binge-watching Korean Drama Series and the incidental vocabulary acquisition of tertiary level learners in the Polytechnic University of the Philippines. The researchers used a non-experimental correlational approach to measure the degree of relationship that exists between the two variables. The results show that the respondents are considered 'moderately knowledgeable' on the specific Korean words and phrases on the survey questionnaire based on the weighted mean response of their Korean Vocabulary Depth. Hence, there is a significant relationship between binge-watching habits of the respondents and their Basic Korean Vocabulary Knowledge Depth. The researchers also concluded that as the binge-watching habits increase, the Basic Korean Vocabulary Knowledge Depth also increases.